The Effect of Probiotics on the Prevention of Necrotizing Enterocolitis (NEC) in Low Birth Weight (LBW) and Very Low Birth Weight (VLBW) Infants - Reza Saeidi; Shamsollah Nouripour; Parinaz Alizadeh (Iranian Journal of Neonatology, 2025)
Background: Necrotizing enterocolitis (NEC) is a life-threatening disease for premature and very low birth weight infants (VLBW).Traditional therapeutic methods such as administration of antibiotics and antacids and cessation of breastfeeding can exacerbate changes in the intestinal microbiota. The mechanisms of action are believed to involve modulation of the gut microbiome, enhancement of the gut barrier function, and immunomodulation. To review the current evidence regarding the use of probiotics for the prevention of NEC in low birth weight (LBW) and VLBW infants. Methods: A literature search was conducted across major databases (MEDLINE, Embase, Cochrane Library), supplemented by hand-searching of relevant articles and review of reference lists. The search encompassed randomized controlled trials (RCTs), meta-analyses, and review articles published up to 2024. This review included studies that investigated the effect of probiotic supplementation on NEC incidence and related outcomes in LBW and VLBW infants. Excluded studies were those of poor methodological quality or that did not report relevant outcomes. Results: In this study, a large number of studies on the effect of probiotics on the prevention of NEC in premature and low birth weight infants were found, which showed beneficial effects of probiotics. And probiotics have reduced the Incidence of NEC, Severity of NEC, Mortality. However, these studies were quite heterogeneous in terms of methodology and type of probiotic used. Adverse events associated with probiotic use were generally infrequent and mild, primarily involving transient diarrhea or vomiting. No significant increase in serious adverse events was reported in any of the included studies. Conclusion: Probiotic supplementation appears to be a beneficial intervention for preventing NEC in LBW and VLBW infants  but yet The decision to use probiotics should be individualized, considering the infant’s risk factors, probiotic availability, and parental preferences.